Preventing the coffee-ring effect and aggregate sedimentation by in situ gelation of monodisperse materials. Issue 39 (5th September 2018) - Li, Huaiguang; Buesen, Darren; Williams, Rhodri; Henig, Joerg; Stapf, Stefanie; Mukherjee, Kallol; Freier, Erik; Lubitz, Wolfgang; Winkler, Martin; Happe, Thomas; Plumeré, Nicolas
Abstract : Microscale uniformity and long-range cohesion in multi-functional films assembled through drop-casting is realized by in situ gelation of monodisperse building blocks. Abstract : Drop-casting and inkjet printing are virtually the most versatile and cost-effective methods for depositing active materials on surfaces. However, drawbacks associated with the coffee-ring effect, as well as uncontrolled aggregation of the coating materials, have impeded the use of these methods for applications requiring high control of film properties. We now report on a simple method based on covalent cross-linking of monodisperse materials that enables the formation of thin films with homogeneous thicknesses and macroscale cohesion. The coffee-ring effect is impeded by triggering gelation of the coating materials via a thioacetate–disulfide transition which counterbalances the capillary forces induced by evaporation. Aggregates are prevented by monodisperse building blocks that ensure that the resulting gel resists sedimentation until complete droplet drying. This combined strategy yields an unprecedented level of homogeneity in the resulting film thickness in the 100 nm to 10 μm range. Moreover, macroscale cohesion is preserved as evidenced by the long-range charge transfer within the matrix. We highlight the impact of this method with bioelectrocatalysts for H2 and NADPH oxidation. Peak catalytic performances are reached at about 10-fold lower catalyst loading compared to conventional approaches owing to the high control on film cohesion and thickness homogeneity, thus setting new benchmarks in catalyst utilization.